PELAKSANAAN FUNGSI KOORDINASI OLEH KEPOLISIAN DENGAN DINAS PERHUBUNGAN DALAM PENERTIBAN LALU LINTAS KOTA PEKANBARU TAHUN 2015-2016 - Maya Syafitri; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Law No. 22 of 2009 on Traffic and Road Transport (LLAJ) expressly mandates POLRI as the main stakeholder of LLAJ to take an active role in efforts to overcome traffic accidents in accordance with the existing authority. With the enforcement of Law Number.22 of 2009 on Traffic and Road Transport in lieu of Law No. 14 of 1992 on Traffic and Road Transport because in view is not in accordance with conditions, environmental changes and the needs of the organizers of traffic and road transport when It is expected that there will be better arrangements in traffic and road transport issues. In this research I will convey how the coordination between the Police and the Department of Transportation related to the security of Traffic Order in accordance with Law No. 22 of 2009 which states that between the Police and the Department of Transportation have been able to work together or coordinate in regulating and disciplining Traffic. This research method using qualitative approach and using type of descriptive research method. Data collection techniques in this study using in-depth interview techniques and relevant fact documentation. Based on the results of interviews and data that researchers have got it can be concluded that the Police and Transportation Department has coordinated well in carrying out the task of controlling traffic in Pekanbaru City 2015-2016. This is evidenced by drawings and warrants that researchers get from both agencies. With good coordination between the two agencies, it is expected that the cooperation between agencies and the public to participate in traffic control on the highway by obeying all regulations and traffic signs that have been set based on Law No. 22 of 2009. Keyword: The Police and the Department of Transportation related to the security of Traffic Order, Traffic Order in accordance